2009
DOI: 10.3897/zookeys.8.110
|View full text |Cite
|
Sign up to set email alerts
|

Roncus elbulli (Arachnida, Pseudoscorpiones), a new species from Cap de Creus Nature Park (Catalonia, Spain), with a key to the Spanish species of the genus Roncus

Abstract: Roncus elbulli sp. n. is described from Cap de Creus Nature Park (Catalonia, Spain). Th e new species is morphologically close to Roncus cadinensis Zaragoza, 2007 (Barcelona province), but diff ers by being smaller in size and having a more robust chela with a diff erent microsetae pattern. Th e new species seems to be restricted to coastal semiarid slopes with garrigue vegetation. A key to the Spanish species of the genus Roncus is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 831 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…Our study provides further information on the cytogenetics of the pseudoscorpion genus Roncus (Neobisiidae) based on a study of another four species, which extends the previous work on this genus that was based on eight species (Troiano, 1990(Troiano, , 1997Zaragoza & Šťáhlavský, 2008). As in the previous study we found differences between the karyotypes that may be useful for future cytotaxonomic studies (Table 1).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our study provides further information on the cytogenetics of the pseudoscorpion genus Roncus (Neobisiidae) based on a study of another four species, which extends the previous work on this genus that was based on eight species (Troiano, 1990(Troiano, , 1997Zaragoza & Šťáhlavský, 2008). As in the previous study we found differences between the karyotypes that may be useful for future cytotaxonomic studies (Table 1).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, all three species have the X0 sex chromosome system with a metacentric X chromosome, which is the smallest element in the karyotypes. This finding contrasts with other species of this genus from Italy (Liguria) (Troiano, 1990(Troiano, , 1997 and Spain (Catalonia) (Zaragoza & Šťáhlavský, 2008). The karyotypes of these species are even more variable.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations